How effective are on-farm conservation land management strategies for preserving ecosystem services in developing countries? A systematic map protocol - Thorn, J.; Snaddon, J.; Waldron, A.; Kok, K.; Zhou W; Bhagwat, S.; Willis, K.; Petrokofsky, G. (Springer, 2015)
An extensive body of literature in the field of agro-ecology claims to show the positive effects that maintenance of ecosystem services can have on sustainably meeting future food demand, by making farms more productive and resilient, and contributing to better nutrition and livelihoods of farmers. In Africa alone, some research has estimated a two-fold yield increase if food producers capitalize on new and existing knowledge from science and technology. Site-specific strategies adopted with the aim of improving ecosystem services may incorporate principles of multifunctional agriculture, sustainable intensification and conservation agriculture. However, a coherent synthesis and review of the evidence of these claims is largely absent, and the quality of much of this literature is questionable. Moreover, inconsistent effects have commonly been reported, while empirical evidence to support assumed improvements is largely lacking.